Urgensity of “Halal Tourism”: Religiosity, Awareness, and Interest from Stakeholders - ZARKASYI, Muhammad Ridlo; KURNIAWAN, Dhika Amalia; DARMA, Dio Caisar (Journal of Environmental Management and Tourism; Vol 12 No 4 (2021): JEMT Volume XII Issue 4(52) Summer 2021DO - 10.14505//jemt.v12.4(52).11, 2021)
The push for the “halal tourism’ attribute in Muslim countries is quite enthusiastic. There are great interest and encouragement from tourists. Explicitly, currently, several regions in Indonesia such as Ponorogo Regency are trying to realize this concept. In this paper, we have the ambition to see how much influence “halal tourism’ has in Ponorogo Regency. Through variable boundaries, the relationship between religiosity, awareness, and interest can be found. This study attempt to reach all stakeholders who are already involved in the tourism sector. The survey approach was carried out by open interviews, where data was collected based on 409 informants. A multiple linear regression model is applied to answer the hypothesis design empirically. As a result, the informants who are divided into 5 groups who have experience in the field of tourism consider the concept of ‘halal tourism’ quite urgent to be revitalized. Other analyzes also found that religiosity and awareness had a significant effect on interest (p <0.05). Awareness plays an important role in the relationship between religiosity and interests. The originality of this invention lies in the elements (variables and items) used, therefore it deserves to be used as a reference at a later date by decision-makers.